A resource of longitudinal RNA-seq data of Holstein cow rumen, duodenum, and colon epithelial cells during the lactation cycle - Yahui Gao; George E. Liu; Li Ma; Cong-jun Li; Ransom L Baldwin (BMC Genomic Data)
Abstract Objective As one of the most important ruminant breeds, Holstein cattle supply a significant portion of milk and dairy for human consumption, playing a crucial role in agribusiness. The goal of our study was to examine the molecular adaptation of gastrointestinal tissues that facilitate milk synthesis in dairy cattle. Data description We performed RNA-seq analysis on epithelial cells from the rumen, duodenum, and colon at eight different time points: Days 3, 14, 28, 45, 120, 220, and 305 in milk, as well as the dry period. Samples were taken from five multiparous dairy cows as biological replicates per tissue per stage, except for Days 14 and 28, for which the sample size was three. These tissues each serve critical and distinct roles in the digestion and absorption of nutrients and are all vital for providing the necessary substrates required for milk production. Understanding the intricate connections between the tissues involved in providing nutrients necessary to support milk synthesis and their role in digestion can deepen the understanding of lactation physiology. This resource aims to deliver in-depth insights into cattle lactation, highlighting the distinct traits of gastrointestinal tissues and illuminating the intricate transcriptomic dynamics throughout the lactation period.